Stress among doctors doing residency: a cross sectional study at a tertiary care hospital in Vijayapura, Karnataka - Tellur, Laxmi; Yadavannavar, M. C.; Sorganvi, Vijaya; Patil, Shailaja (International Journal Of Community Medicine And Public Health, 2022)
Background: Young budding doctors doing residency is a very stressful period. There is growing concern about stress in doctors working in hospitals. So, this study was carried out to study the proportion of stress and associated factors influencing stress among resident doctors at a tertiary care hospital in Vijayapura, Karnataka. Methods: A cross-sectional study was conducted in BLDE (Deemed to be University), Shri B. M. Patil medical college, hospital and research centre, Vijayapura from July 2019 to December 2019. The perceived stress scale, 10-item self report questionnaire was used to assess the level of stress. analysis was done using SPSS 16. Results: A total of 207 post graduate residents were interviewed.90% of postgraduate students responded and all were above the age of 24 years. 52.7% were males and 47.3% were females. Of all postgraduates 91.3% were Hindu, 5.3% were Muslim by religion. Our study has revealed more stress among 2nd year resident doctors. Conclusions: Fixed duty hours, counselling and social support can help in improving the physical and mental well-being of these young doctors, who are an integral part of the health care system. Stress should be evaluated to get better future health consultants.